2000
DOI: 10.1103/physrevb.61.r2413
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide diffusion modes and slowdown of D’yakonov-Perel’ spin relaxation in narrow two-dimensional semiconductor channels

Abstract: We have shown that in narrow 2D semiconductor channels the D'yakonov-Perel' spin relaxation rate is strongly reduced. This relaxation slowdown appears in special waveguide diffusion modes which determine the propagation of spin density in long channels. Experiments are suggested to detect the theoretically predicted effects. A possible application is a field effect transistor operated with injected spin current.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
73
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 14 publications
3
73
0
Order By: Relevance
“…However, as Mal'shukov et al pointed out, other mechanisms can limit the eventual suppression of the spin relaxation, e.g., the BIA induces a component of the D'yakonov-Perel' spin relaxation which is independent of the channel width [20]. We would like to note that in a first experimental study, an effective slowing of the Dyakonov Perel spin relaxation mechanism has been observed in conducting channels of n-InGaAs quantum wires [22,44].…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…However, as Mal'shukov et al pointed out, other mechanisms can limit the eventual suppression of the spin relaxation, e.g., the BIA induces a component of the D'yakonov-Perel' spin relaxation which is independent of the channel width [20]. We would like to note that in a first experimental study, an effective slowing of the Dyakonov Perel spin relaxation mechanism has been observed in conducting channels of n-InGaAs quantum wires [22,44].…”
mentioning
confidence: 98%
“…Here, we describe the possibility of an effective suppression of the spin relaxation in the two-dimensional conducting channel of a spin transistor [18][19][20][21]. As a precursor of the one-dimensional limit, long spin relaxation times are expected when the channel width w is smaller than the electronic mean free path l e (w < l e ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is accompanied by spin polarization oscillations and spin polarization transfer from the perpendicular to in-plane component. The prospects for creating a semiconductor-based spintronic device [1,2,3,4,5,6] have generated an emphasis on the studies of properties of electron spin polarization in semiconductor nanostructures [7,8,9,10,11,12,13,14,15,16,17]. Great interest has been expressed in dynamics of electron spin polarization [7,8,9,10,11,12].…”
mentioning
confidence: 99%
“…In an n-doped bulk semiconductors τ sb can be very long [9], and a large L s will reduce the efficiency of spin injection. This is the same problem encountered in the study of spin injection from ferromagnetic metals into semiconductors [3], which can be overcome [4] with a proper choice of the barrier height…”
mentioning
confidence: 99%